Closing the Gender gap seminar: Sonja Vermeulen - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Discussion around the research gaps & key findings that have relevance to current policy processes - Sonja Vermeulen, Head of Research, CCAFS, at the Closing the gender gap in farming under climate change event held 19 March 2015 in Paris Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action